ANALYSING THE RELATION OF OPERATIONAL AND ECONOMIC PARAMETERS TO TOTAL SHAREHOLDER VALUE OF LISTED GOLD MINING COMPANIES IN INDONESIA AND FIVE OTHER COUNTRIES - Antonius Siahaan (Ultima Management : Jurnal Ilmu Manajemen, 2020)
Even though Indonesia was famous due to its mineral resources, only few gold mining companies is listed in the Indonesia stock exchange. In the other hand, there is a need to increase investment in the mining sector from stock market as reserve has been stagnant while production keeps going. To understand the nature of published gold mining companies, this study is conducted to analyze the effect of published operational parameter: ore processed, gold production, mining grade, process recovery, as well as external factors such as gross-domestic product and gold price to the share return of public listed gold mining companies. From panel data regression of quarter reports of eighteen (18) world mining companies in the period 2012 to 2017, it shows that process recovery and gold price is significant to the change of share price. Furthermore, the study finds that when operational parameter of existing mines can be good and positively increase, mining companies still need to look at their reserve to ensure sustainability of the business in the long run. Key Words: Public Listed Gold Company, Share Return, Panel Data Regression, Operational Parameters, External Factors